Distinct behavioral response of primary motor cortex stimulation in itch and pain after burn injury. (18th January 2019) - Thibaut, Aurore; Ohrtman, Emily A.; Morales-Quezada, Leon; Simko, Laura C.; Ryan, Colleen M.; Zafonte, Ross; Schneider, Jeffrey C.; Fregni, Felipe
Highlights: Chronic neuropathic pain and itch are two of the most commonly reported challenges following a burn injury. There is still a lack of effective treatment for neuropathic pain and itch. M1 tDCS has shown to reduce neuropathic pain in various etiologies in previous studies. In post-burn neuropathic pain, tDCS did not modulate pain, while a placebo effect was found for itch. Post-burn neuropathic pain and itch are modulated by different neural circuits and should be treated accordingly. Abstract: It is still unclear whether chronic neuropathic pain and itch share similar neural mechanisms. They are two of the most commonly reported challenges following a burn injury and can be some of the most difficult to treat. Transcranial direct current stimulation (tDCS) has previously been studied as a method to modulate pain related neural circuits. Therefore, we aimed to test the effects of tDCS on post-burn neuropathic pain and itch as to understand whether this would induce a simultaneous modulation of these two sensory manifestations. We conducted a pilot randomized controlled clinical trial comprised of two phases of active or sham M1 tDCS (Phase I: 10 sessions followed by a follow-up period of 8 weeks; Phase II: additional 5 sessions followed by a follow-up period of 8 weeks, and a final visit 12 months from baseline). Pain levels were assessed with the Brief Pain Inventory (BPI) and levels of itch severity were assessed with the Visual Analogue Scale (VAS). Measurements were collected at baseline, after the stimulation periods, at 2, 4 and 8-week follow up both for Phase I and II, and at the final visit. Sixteen patients were assigned to the active group and 15 to the sham group. Ten sessions of active tDCS did not reduce the level of pain or itch. We identified that itch levels were reduced at 2-week follow-up after the sham tDCS session, while no placebo effect was found for the active group. No difference between active and sham groups was observed for pain. We did not find any treatment effects during Phase II. Based on these findings, it seems that an important placebo effect occurred during sham tDCS for itch, while active M1 tDCS seems to disrupt sensory compensatory mechanisms. We hypothesize that pain and itch are complementary but distinct mechanisms of adaptation after peripheral sensory injury following a burn injury and need to be treated differently.